Application of Queueing Model to an Outpatient Flow in a Multi-Speciality Hospital (Journal of Pharmaceutical Negative Results, 2022)
Waiting in line is now becoming a common problem in our daily life and long waiting in queues results in loss of customers, bad reputation etc. Hence queuing and waiting time analysis is particularly important in service systems. Management of queues plays a critical role in the health care management as it deals with the issue of treatment of patients to provide better assistance. This research aims to study the outpatient department of a multi-specialty hospital in Kerala using a single line multiple server queue. For the study, we have collected the data on arrivals, waiting time, service pattern and departures during 7 days (considering 3 servers) from 9.00 am to 3.00 pm and used them as input data in the M/M/C model. The computation of performance measures corresponding to M/M/1, M/M/2 and M/M/3 queuing models shows the average waiting time of patients in the queue and system, the average length of queue and system, the percentage of server utilization, etc. can be reduced by incrementing the number of servers. Also, the plot of delay probability with the number of servers and arrival rate shows that delay probability decreases if the number of servers increases and increases with the increase of arrival rate. The analysis of the study of hospital data using queuing models shows that instead of having three doctors at present there is a need for a minimum of seven doctors to reduce the delay time of patients and thus get the facility immediately.